2018
DOI: 10.3389/fpubh.2017.00368
|View full text |Cite
|
Sign up to set email alerts
|

The Border Health Consortium of the Californias—Forming a Binational (California–Baja California) Entity to Address the Health of a Border Region: A Case Study

Abstract: The California–Baja California border region is one of the most frequently traversed areas in the world with a shared population, environment, and health concerns. The Border Health Consortium of the Californias (the “Consortium”) was formed in 2013 to bring together leadership working in the areas of public health, health care, academia, government, and the non-profit sector, with the goal of aligning efforts to improve health outcomes in the region. The Consortium utilizes a Collective Impact framework which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…79,11,1922 Indeed, even with a good vaccine coverage (78–83%), the impact of PCV13 on PnPE in our population was rapid. We do not have a concise explanation for that result, but maybe there is indirect immunization from vaccinees coming from San Diego, California (the highest-transit border in the world), 1213 a city with a much longer PCV13 immunization time than Tijuana, but again, this is a mere speculation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…79,11,1922 Indeed, even with a good vaccine coverage (78–83%), the impact of PCV13 on PnPE in our population was rapid. We do not have a concise explanation for that result, but maybe there is indirect immunization from vaccinees coming from San Diego, California (the highest-transit border in the world), 1213 a city with a much longer PCV13 immunization time than Tijuana, but again, this is a mere speculation.…”
Section: Discussionmentioning
confidence: 95%
“…The Tijuana, Mexico-San Diego, California (USA) border is the busiest crossing in the world and has very relevant health issues that concern both countries. [12][13][14] Material and methods From 1 October 2005 to 31 January 2018 (12.3 years) we performed active/prospective surveillance for all pediatric (<16 years of age) cases of PE at the General Hospital of Tijuana, Mexico. Surveillance was developed as follows: once a patient < 16 years of age was admitted with a clinical/radiological diagnosis of community-acquired pneumonia complicated with pleural effusion, a chest puncture was promptly performed, if a purulent extraction or PF with more than 1000 leukocytes was obtained (defined as case), an immediate inoculation of pleural fluid (PF) into a radiometric broth media (BACTEC®, Becton Dickinson, Franklin Lakes, NJ, USA) was followed, and incubated at 37°C with 5% CO 2 , with final identification performed using Vitek/Microscan Vitek2®, BioMérieux, Hazelwood, Missouri, USA,).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant perspective on leaders’ meaning making role, in both the leadership and the meaningfulness literature, focuses on leaders’ positive influence on followers’ work meaningfulness. This line of research has shown that transformational leadership, empowering leadership, and high-quality leader-member relationships are positively related to followers’ perceptions of work meaningfulness (e.g., Piccolo and Colquitt, 2006 ; Arnold et al, 2007 ; Grant, 2012 ; Tummers and Knies, 2013 ). However, research on the dark side of leaders’ meaning making is scarce (for exceptions, see Amabile and Kramer, 2012 ; Neal et al, 2013 ; Bailey and Madden, 2016 ).…”
Section: Introductionmentioning
confidence: 98%
“…Studies on the cultivation of work meaningfulness have mostly focused either on work conditions (e.g., May et al, 2004 ; Humphrey et al, 2007 ), on individuals’ personal behaviors (e.g., Vuori et al, 2012 ) that increase their sense of meaningfulness, or on a combination of both (e.g., Chalofsky and Krishna, 2009 ) as antecedents to work meaningfulness. Studies that have addressed leadership as an antecedent, have generally focused on how leaders help construct work meaningfulness among followers and contribute to their sense of meaning (e.g., Shamir et al, 1993 ; Zhang and Bartol, 2010 ; Tummers and Knies, 2013 ). There are different views of leaders’ role in meaning making and how meaning making leads to meaningful work.…”
Section: Introductionmentioning
confidence: 99%